Gulls as indicators of environmental changes in the North Atlantic: a long-term study on Berlenga Island, Western Portugal - Ceia, Filipe R. (2023)
In recent decades, the breeding populations of the yellow-legged gull Larus michahellis (YLG) have increased significantly, primarily due to the increase in open refuse dumps and discards from fisheries. Portugal’s largest YLG breeding colony is located on Berlenga Island, where population numbers have been monitored since 1974. The population grew exponentially until 1994, prompting the implementation of population control measures, including culling adult birds and eggs. A long-term data base including number of breeding birds (since 1974), breeding parameters (since 2002), and trophic niches (using stable isotopes since 2011) of YLG breeding on Berlenga was related with oceanographic parameters, fish landings and quantity of urban waste. Trophic ecology showed strong relationships with oceanographic parameters (wNAO, Chl-a, and SST) and fisheries landings (the 10 most frequently consumed species by the YLG, traded at fish auctions in the main fishing harbour nearby). The results indicated significant relationships between reproductive performance and fisheries landings, particularly with demersal species that gulls primarily access through fisheries discards. However, population control measures played a pivotal role in stabilising and even reducing the population, despite sporadic events of poor oceanographic productivity in the past decade having a consistent impact on the reduction in breeding individuals.